Pengukuran Modal Manusia (Suatu Studi Literatur) - Evi Adriani (J-MAS (Jurnal Manajemen dan Sains), 2019)
Human capital is an investment in the field of human resources The process of acquiring knowledge and skills through education is not merely a consumptive activity, but rather a form of investment in Human Resources (HR). This study will explain the existence of the theory of human capital in terms of investment in human capital for education. Explanation starts from the definition and concept of human capital, perspective in discussing human capital investment and methods of measuring human capital investment. This paper closes with the signaling theory which is another direction of thinking about the role of education as human capital.